Electronic Vaping-Induced Methicillin-Sensitive Staphylococcus Aureus Pneumonia and Empyema - Sachin M. Patil; Phillip Paul Beck; Tarang Pankaj Patel; Richard Dale Swaney; Dima Dandachi; Armin Krvavac (Case Reports in Infectious Diseases)
Pneumonia is a severe acute inflammation of the lower respiratory tract due to infectious pathogens. Pathogens responsible include bacteria, viruses, fungi, and parasites. Pneumonia categorizations include community-acquired pneumonia (CAP), hospital-acquired pneumonia, and ventilator-associated pneumonia. It is the single most common cause of infection-related mortality in the United States. Among the typical bacterial CAP causes, Staphylococcus aureus (S. aureus) is responsible for less than 5% of all cases. Among the S. aureus, methicillin-susceptible S. aureus (MSSA) is slightly more common than the methicillin-resistant S. aureus (MRSA). CAP caused by S. aureus is associated with worse clinical outcomes compared to streptococcal pneumoniae. Although S. aureus CAP occurs throughout the year, it is less common except during the influenza season when there is a spike. Multiple studies have stratified risk factors for MRSA infection. MSSA pneumonia in immunocompetent young patients is uncommon due to healthy host defense mechanisms. However, certain individual risk factors promote infection, such as intravenous drug abuse. Recent multiple research studies implicate increased virulence of S. aureus in colonized patients after exposure to electronic cigarette vapor exposure (ECVE), resulting in pneumonia. A PubMed search revealed no MSSA community-acquired bacterial pneumonia due to ECVE. We report a 38-year-old female who developed acute MSSA pneumonia, which was complicated by left empyema due to ECVE from JUUL device with third-party compatible cannabidiol pods. The patient completed treatment successfully with a chest tube placement followed by fibrinolysis and intravenous antibiotics.